Effectivity of ozone water application on the socket after posterior tteeth extraction to accelerate clotting time phase - Isnandar Isnandar; Rahmi Syaflida; Abdullah Oes; Yuni Nurul Fairuz (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
After tooth extraction, dentists always place sterile tampons on the extracted socket to stop bleeding, to prevent infection and to reduce patients’ discomfort. Ozone is a biocompatible, bactericidal gas that can accelerate the healing of wounded soft tissue. In addition, it comes up with hemostasis effect to stop bleeding and may accelerate the clotting time and wound healing. Another advantage of ozone therapy is that it can be treated without making any trauma. The purpose of this research is to evaluate the effectivity of ozone water application in the socket to accelerate clotting time phase after posterior teeth extraction in 3 minutes, 6 minutes, and 10 minutes. This research was clinical experimental research with post-test only control group design. The research sampling was done through non-probability sampling. Then, sample was divided into two groups, each of which consisted of 15 patients treated with ozone tampons and 15 patients treated with sterile tampons after tooth extraction. Data were analyzed using chi-square test, and results showed a significant difference between the two groups. Ozone tampons show better result in accelerating clotting time after posterior teeth extraction than sterile tampons.